2008
DOI: 10.1088/0953-8984/20/42/425219
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of spin–phonon coupling in ErMnO3

Abstract: ErMnO3 single crystals are studied by polarized first-order and second-order micro-Raman measurements as a function of temperature and compared to previous hexagonal RMnO3 (R =  Y, Ho, Yb) studies. In addition to the resonance effects of the 684 cm−1 mode that are correlated with Mn3+ d–d electronic transitions, some phonon frequencies show anomalous temperature variations suggesting a spin–phonon coupling below TN. The deviation from standard temperature dependence is discussed within a model accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 32 publications
5
37
1
Order By: Relevance
“…We note that this identification is consistent with the modes reported in reference 16 from FIR spectroscopy, except for the weaker modes E 1 and E 8 [25]. Finally, around 125 cm −1 a larger phononic band is observed in agreement with Ab initio calculation [26] and Raman spectroscopy [27].…”
supporting
confidence: 91%
“…We note that this identification is consistent with the modes reported in reference 16 from FIR spectroscopy, except for the weaker modes E 1 and E 8 [25]. Finally, around 125 cm −1 a larger phononic band is observed in agreement with Ab initio calculation [26] and Raman spectroscopy [27].…”
supporting
confidence: 91%
“…Raman and infrared absorption investigations of the temperature dependent phonon spectrum of YMnO 3 and LuMnO 3 have found a kink at and an abnormal hardening in the magnetically ordered phase, indicating strong spinphonon coupling [163][164][165]. Similar phonon hardening was also found in compounds with rare earth magnetic moments, HoMnO 3 and ErMnO 3 [128,166]. 3 .…”
Section: +mentioning
confidence: 60%
“…On the other hand, there is also evidence for strong spin lattice interactions as, for example, shown in the phonon hardening below [166]. This could explain the anomalies of the dielectric constant at the various phase boundaries, similar to other rare earth manganites.…”
Section: Multiferroic Properties and Phase Diagrams Of Ermnomentioning
confidence: 76%
“…The in-plane bonding force constants would be closely related with the lattice constant a, and the inter-plane bonding force constants with the lattice constant c. Therefore, our results suggest that, in hexagonal RMnO 3 thin films, both the lattice constants a and c would show a systematic variation with R, and the lattice constant c would have a weaker R dependence. The phonon scattering in hexagonal RMnO 3 has been investigated for various R ions, R = Y, [25,26] R = Ho, [27] R = Er, [28] R = Yb, [29] and R = Lu. [30] Comparing the phonon peak positions in these reported studies, we noticed that almost all the observed phonons did not show any systematic variation with R, contrary to our experimental findings.…”
Section: Resultsmentioning
confidence: 99%
“…[17,19 -20] Hexagonal RMnO 3 have ferroelectric properties with a fairly large remnant polarization and quite high Curie temperature (T C ), typically above 590 K. Hexagonal RMnO 3 also exhibit antiferromagnetic behaviors, while their Néel temperature (T N ) is low, in the range of 70-120 K, probably due to geometrical frustration. [3] The phonon scattering in hexagonal RMnO 3 has been investigated for various R ions, R = Y, [25 -26] R = Ho, [27] R = Er, [28] R = Yb, [29] and R = Lu. [30] However, to our knowledge, there is no systematic study on the R dependence of the phonon scattering in hexagonal RMnO 3 .…”
Section: Introductionmentioning
confidence: 99%